Vinyl chloride resin composition

The vinyl chloride resin composition, formulated with specific ratios of trimellitic acid and polyester plasticizers, addresses the challenges of sebum and sweat resistance, cold, and heat resistance, resulting in a durable and resistant material for automotive interiors.

JP2025038636APending Publication Date: 2025-03-19SHIN ETSU POLYMER CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023145367
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Vinyl chloride resin compositions used in molded products face challenges with resistance to sebum and sweat, leading to issues like discoloration and deterioration, while also requiring both cold and heat resistance.

Method used

A vinyl chloride resin composition is developed, comprising a vinyl chloride resin, a trimellitic acid plasticizer, and a polyester plasticizer, with the trimellitic acid plasticizer content ranging from 30 to 70% by mass, which enhances cold and heat resistance while maintaining oleic acid resistance.

Benefits of technology

The composition achieves high resistance to oleic acid contained in sebum and sweat, along with excellent cold and heat resistance, making it particularly suitable for interior automotive components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038636000001
    Figure 2025038636000001
Patent Text Reader

Abstract

To provide a vinyl chloride resin composition suitable for producing a molded article having less deterioration due to sebum and sweat adhesion and having both cold resistance and heat resistance.SOLUTION: There is provided a vinyl chloride resin composition which comprises a vinyl chloride-based resin, a trimellitic acid-based plasticizer, and a polyester-based plasticizer, wherein the content of the trimellitic acid-based plasticizer is 30 to 70 mass% with reference to the total content of the trimellitic acid-based plasticizer and the polyester-based plasticizer. The trimellitic acid-based plasticizer preferably has a linear alkyl group in the molecule.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vinyl chloride resin composition having improved resistance to sebum and sweat. [Background technology]

[0002] Conventionally, vinyl chloride resin compositions have been used in molded articles such as automobile parts and electronic / electrical device parts, and in covering materials for communication cables, electric wires, etc. (for example, Patent Document 1). Among these molded articles, those that are frequently touched by people may be required to have resistance to sebum and sweat. Since sebum and sweat contain free fatty acids (especially oleic acid), problems such as discoloration and deterioration may occur if the molded article is left in contact with the free fatty acids. In addition, these molded articles may be required to have both cold resistance and heat resistance at the same time. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-070066 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a vinyl chloride resin composition which is less susceptible to deterioration due to adhesion of sebum or sweat and is suitable for producing molded articles which have both cold resistance and heat resistance. [Means for solving the problem]

[0005] [1] A vinyl chloride resin composition comprising a vinyl chloride resin, a trimellitic acid plasticizer, and a polyester plasticizer, wherein the content of the trimellitic acid plasticizer is 30 to 70 mass% relative to the total content of the trimellitic acid plasticizer and the polyester plasticizer. [2] The vinyl chloride resin composition according to [1], wherein the trimellitic acid-based plasticizer has a linear alkyl group in the molecule. [3] The vinyl chloride resin composition according to [1] or [2], which has a brittle temperature of -35°C or lower, measured in accordance with JIS K 7216:1980. [4] The vinyl chloride resin composition according to any one of [1] to [3], wherein the polyester plasticizer has a viscosity of 1000 to 5000 mPa s at 25°C. [5] The vinyl chloride resin composition according to any one of [1] to [4], wherein in a heat resistance test in which a test piece formed into a sheet from the vinyl chloride resin composition is kept in a heating chamber at 120°C for 400 hours, the weight loss rate, expressed as the weight of the test piece after the heat resistance test relative to the weight of the test piece before the heat resistance test, is 2.0% by weight or less. [6] The vinyl chloride resin composition according to any one of [1] to [5], wherein in a test in which a test piece obtained by molding the vinyl chloride resin composition into a sheet shape is immersed in oleic acid at 80°C for 70 hours, the weight loss rate, expressed as the weight of the test piece after immersion relative to the weight of the test piece before immersion, is 20% by weight or less. Effect of the Invention

[0006] The vinyl chloride resin composition of the present invention has high resistance to oleic acid contained in sebum and sweat, and has both cold resistance and heat resistance, making it particularly useful as an automobile interior material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] <Vinyl chloride resin composition> A first aspect of the present invention is a vinyl chloride resin composition (hereinafter sometimes referred to as a "PVC composition") containing a vinyl chloride resin, a trimellitic acid plasticizer, and a polyester plasticizer.

[0008] In this embodiment, the content of the trimellitic acid-based plasticizer relative to the total content of the trimellitic acid-based plasticizer and the polyester-based plasticizer is preferably 30 to 70 mass%, more preferably 40 to 65 mass%, and even more preferably 45 to 60 mass%. When the content of the trimellitic acid-based plasticizer is equal to or more than the above lower limit, the cold resistance and heat resistance are further improved. When the content of the trimellitic acid-based plasticizer is equal to or less than the upper limit, the oleic acid resistance is further improved.

[0009] In this embodiment, the total content of the trimellitic acid-based plasticizer and the polyester-based plasticizer relative to 100 parts by mass of the vinyl chloride-based resin is preferably 40 to 200 parts by mass, more preferably 60 to 150 parts by mass, even more preferably 70 to 100 parts by mass, and most preferably 80 to 95 parts by mass. When the total content is at least the lower limit of the above range, the processability and flexibility of the PVC composition are further improved. When the total content is equal to or less than the upper limit of the above range, the inherent rigidity and hardness of the vinyl chloride resin can be utilized.

[0010] The PVC composition of this embodiment may contain other plasticizers in addition to the trimellitic acid plasticizer and the polyester plasticizer. As the other plasticizer, for example, it is preferable to contain an epoxy plasticizer. The content of the other plasticizer is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, further preferably 3 to 10 parts by mass, and most preferably 4 to 9 parts by mass, relative to 100 parts by mass of the vinyl chloride resin. Within the above preferred range, the processability and flexibility of the PVC composition can be further improved without impairing the cold resistance, heat resistance, and oleic acid resistance exhibited by the trimellitic acid plasticizer and the polyester plasticizer.

[0011] Trimellitic acid-based plasticizers include trimellitic acid alkyl esters. The alkyl group constituting the alkyl ester is not limited, but has a carbon number of 1 or more, preferably 2 to 20. The alkyl group may be linear or branched, but is preferably linear from the viewpoint of enhancing the cold resistance and heat resistance of the PVC composition of this embodiment.

[0012] Trimellitic acid has three carboxyl groups. The carboxyl groups of trimellitic acid react with alcohol to form an alkyl ester. One molecule of trimellitic acid alkyl ester has 1 to 3 alkyl groups. The multiple alkyl groups in one molecule may be the same or different. In addition, the hydrogen atoms constituting the alkyl groups may be substituted with other functional groups or halogen elements.

[0013] Specific examples of trimellitic acid alkyl esters include tri-normal octyl trimellitate, tri-normal nonyl trimellitate, tri-normal decyl trimellitate, tri-isooctyl trimellitate, tri-isononyl trimellitate, tri-isodecyl trimellitate, tri-(2-ethylhexyl) trimellitate, trimellitic acid-mixed linear alkyl, etc. Trimellitic acid-mixed linear alkyl has multiple types of linear alkyl groups in one molecule (for example, a combination of two or three types of normal octyl group, normal nonyl group, and normal decyl group).

[0014] The polyester plasticizer is a plasticizer other than trimellitic acid alkyl ester, and is a compound different from the trimellitic acid plasticizer. For example, it is preferable that the polyester chain formed by the reaction of polyhydric alcohol and dicarboxylic acid is present in the molecule. It is preferable that the polyester plasticizer has two ester bonds in one molecule.

[0015] Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-hexanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and neopentyl glycol.

[0016] Examples of dicarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0017] From the viewpoint of enhancing the oleic acid resistance of the PVC composition of this embodiment, an adipic acid polyester plasticizer using adipic acid is preferred.

[0018] From the viewpoint of increasing the oleic acid resistance of the PVC composition of this embodiment, the viscosity (25°C) as an index correlated with the molecular weight of the polyester-based plasticizer is preferably 1000 to 5000 mPa·s, more preferably 2000 to 4000 mPa·s, even more preferably 2500 to 3500 mPa·s, and most preferably 2800 to 3200 mPa·s.

[0019] The vinyl chloride resin may be a homopolymer of vinyl chloride (PVC) or a copolymer. Examples of copolymerizable monomers include ethylene, propylene, acrylonitrile, vinyl acetate, maleic acid or its ester, acrylic acid or its ester, methacrylic acid or its ester, vinylidene chloride, etc.

[0020] The vinyl chloride resin of this embodiment is preferably a vinyl chloride homopolymer. When it is a copolymer, the content of repeating units other than vinyl chloride is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of repeating units derived from vinyl chloride. The vinyl chloride resin of the present embodiment may be chlorinated after the resin is formed.

[0021] The average polymerization degree of the vinyl chloride resin of this embodiment is not particularly limited, but is, for example, preferably 1000 to 4000, more preferably 1200 to 3000, and even more preferably 1300 to 2000. When the average polymerization degree is within the above preferred range, it becomes easy to obtain a hardness suitable for automobile interior members. Here, the average degree of polymerization of the vinyl chloride resin is the average degree of polymerization measured in accordance with JIS K6720-2. The average degree of polymerization is calculated from the K value. The K value is a value measured in accordance with JIS K7367-2 (ISO1628-2).

[0022] The content of the vinyl chloride resin relative to the total mass of the PVC composition of this embodiment is preferably 25 to 53 mass%, more preferably 30 to 50 mass%, further preferably 35 to 48 mass%, and most preferably 40 to 45 mass%. When in the above preferred range, the blending ratio with other components becomes appropriate, and cold resistance, heat resistance, and oleic acid resistance are easily obtained.

[0023] The PVC composition of this embodiment may contain a resin other than the vinyl chloride-based resin. From the viewpoint of fully obtaining the effects of the present invention, the content of the resin other than the vinyl chloride-based resin is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the vinyl chloride-based resin.

[0024] The PVC composition of this embodiment may contain any additives, such as a heat stabilizer, a processing aid (lubricant), an ultraviolet absorber, a light stabilizer, an antioxidant, a crystal nucleating agent, an antistatic agent, a metal deactivator, a filler such as calcium carbonate, an antibacterial agent, or a pigment, as long as the effects of the present invention are not impaired.

[0025] Examples of the heat stabilizer include a lead-based stabilizer, a tin-based stabilizer, a silver-based stabilizer, a calcium-magnesium-zinc-based stabilizer, a calcium-zinc-based stabilizer, a barium-zinc-based stabilizer, a barium-cadmium-based stabilizer, and a hydrotalcite-based stabilizer. The heat stabilizer may be contained alone or in combination with two or more kinds. The total content of the heat stabilizer is preferably from 0.1 to 8 parts by mass, more preferably from 1 to 5 parts by mass, and even more preferably from 1 to 3 parts by mass, based on 100 parts by mass of the vinyl chloride resin.

[0026] Examples of processing aids include acrylic lubricants such as methyl acrylate and methyl methacrylate, fatty acid amide lubricants such as stearic acid amide and oleic acid amide, waxes such as paraffin wax, polyolefin wax, ester wax, montanic acid wax, and polyethylene wax, higher fatty acids such as stearic acid and behenic acid, higher alcohols such as stearyl alcohol and cetyl alcohol, fatty acid esters such as butyl stearate and monoglyceride stearate, metal soaps such as calcium stearate and magnesium stearate, and oils such as silicone oil and process oil. One type of processing aid may be included, or two or more types may be included. The total content of the processing aids is preferably 0.1 to 8 parts by mass, more preferably 1 to 5 parts by mass, and even more preferably 1 to 3 parts by mass with respect to 100 parts by mass of the vinyl chloride-based resin.

[0027] <Method for Producing PVC Composition> The method for producing the PVC composition of this embodiment is not particularly limited, and it can be obtained by mixing and kneading by a conventional method so that each component becomes uniform in the composition. Examples of the method for mixing and kneading the vinyl chloride-based resin, each plasticizer, and other auxiliaries include methods using a pressure kneader, a Banbury mixer, etc. When mixing, it is preferable to mix and knead at a resin temperature of 180°C or lower from the viewpoint of preventing the decomposition of PVC.

[0028] <Form of PVC Composition> Specific forms of the PVC composition of this embodiment may be pellets, beads, or powders that are easily subjected to other molding processes, or molded products molded by known molding methods such as press molding, injection molding, and extrusion molding. The molded product is not particularly limited, and examples include automotive interior members, electronic and electrical equipment parts such as personal computers and copy machines, and coating materials for electric wires and cables. The PVC composition of this embodiment is particularly useful as an automotive interior member because it has excellent cold resistance, heat resistance, and oleic acid resistance.

[0029] <Physical properties of the PVC composition> (Cold resistance; embrittlement temperature) Using the PVC composition of this embodiment, a test piece of Type A defined in JIS K 7216:1980 (Test method for embrittlement temperature of plastics) is produced, and the embrittlement temperature is measured according to the same standard, whereby the cold resistance of the PVC composition of this embodiment can be evaluated. The lower the embrittlement temperature of the PVC composition of this embodiment, the more preferable it is, preferably -35°C or lower, more preferably -40°C or lower, and even more preferably -45°C or lower.

[0030] (Heat resistance) Using the PVC composition of this embodiment, a sheet-like test piece is produced, and the test piece is held in a heater capable of heating (for example, 120°C) in an air atmosphere for a predetermined period (for example, 400 hours), and the weight loss rate of the test piece is calculated from the following formula, whereby the heat resistance of the PVC composition of this embodiment can be evaluated. Usually, volatile components volatilize from the test piece by heating, and the weight of the test piece becomes lighter. Formula: {(weight before heating) - (weight after heating)} ÷ (weight before heating) × 100% The lower the weight loss rate of the PVC composition of this embodiment before and after the above heating, the more preferable it is, preferably 2.0% or lower, more preferably 1.8% or lower, and even more preferably 1.5% or lower.

[0031] (Oleic acid resistance) Using the PVC composition of this embodiment, a sheet-like test piece is produced, and the test piece is immersed in heated oleic acid (for example, 80°C) for a predetermined period (for example, 70 hours), and the weight loss rate of the test piece is calculated from the following formula, whereby the oleic acid resistance of the PVC composition of this embodiment can be evaluated. Formula: {(weight before immersion) - (weight after immersion)} ÷ (weight before immersion) × 100% The lower the weight loss rate of the PVC composition of this embodiment before and after the above immersion, the more preferable it is, preferably 20% or lower, more preferably 15% or lower, and even more preferably 8% or lower.

Examples

[0032] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.

[0033] Details of the raw materials listed in Table 1 are as follows. "PVC with a degree of polymerization of 1300" is GR-1300S manufactured by Shin-Etsu Chemical Co., Ltd. The "linear trimellitic acid plasticizer" is W-760 manufactured by DIC, a compound in which the hydrogen atoms of the three carboxyl groups of trimellitic acid are substituted with linear alkyl groups. The "polyester plasticizer" is ADEKA's PN-1030, a plasticizer with polyester chains formed by the polymerization of adipic acid and polyhydric alcohol in the molecule. It has a viscosity of 3000 mPa·s at 25°C and a freezing point of -25°C. "Epoxidized soybean oil" is Chemicizer SE-100 manufactured by Sanwa Synthetic Chemical Industry Co., Ltd., an epoxy-based plasticizer having a triglyceride structure. "Ba-Zn stabilizer 1" is Adeka STAB AC-299 manufactured by ADEKA Corporation, and is a general-purpose heat stabilizer. "Ba-Zn stabilizer 2" is Adeka STAB AP-550 manufactured by ADEKA Corporation, and is a general-purpose heat stabilizer. The "benzotriazole-based ultraviolet absorber" is KEMISORB 79 manufactured by ADEKA Corporation, which is a general-purpose ultraviolet absorber. The "acrylic processing aid" is Mitsubishi Chemical's Metablen P-530A, whose long molecular chains become entangled with the PVC molecules of the matrix resin, creating a pseudo-crosslinked state and imparting melt elasticity. "Calcium carbonate" is Whiten-SB manufactured by Shiraishi Calcium Co., Ltd., a general-purpose filler. "Methylphenylpolysiloxane" is KF-54 manufactured by Shin-Etsu Chemical Co., Ltd. and is a type of silicone oil. "Pigment" is Resinocolor Black HE-451-C, a black pigment.

[0034] <Preparation of Composition> The raw materials were mixed in the amounts (parts by mass) shown in Table 1 using a twin-screw kneader to obtain a PVC composition. For example, in Example 1, 60 parts by mass of trimellitic acid plasticizer, 30 parts by mass of polyester plasticizer, 5 parts by mass of epoxidized soybean oil, and 30.9 parts by mass of other auxiliary agents (stabilizers 1 and 2, UV absorber, acrylic processing aid, calcium carbonate, silicone oil, pigment) were blended with 100 parts by mass of PVC to obtain the target PVC composition, totaling 225.9 parts by mass.

[0035] <Creating a sheet> 100 g of the PVC composition of each test example was kneaded for 10 minutes with a 3.5-inch roll set at 155 ° C to prepare a sheet with a thickness of 0.5 mm. The sheet prepared here can be distinguished between the direction in which it passed through the roll (flow direction) and the direction perpendicular thereto. A plurality of sheets were prepared, stacked in a state in which the flow directions of directly contacting sheets cross each other, preheated at 170 ° C for 4 minutes, and then heat-compressed and molded at 170 ° C and 15 MPa for 4 minutes, and then slowly cooled to room temperature (25 ° C) while still under pressure to obtain a sheet of a predetermined thickness specified for each test, which was then subjected to tests for cold resistance, heat resistance, and oleic acid resistance.

[0036] <Cold resistance; embrittlement temperature> In accordance with JIS K 7216:1980 (Test method for brittle temperature of plastics), the brittle temperature was determined using A-type test pieces specified in the same standard.

[0037] <Heat resistance> The test specimens used were sheet-shaped test specimens with dimensions of 30 mm x 30 mm and thickness of 2 mm, prepared as described above. The weight of the test specimens was measured in advance and they were kept in a heating chamber at 120°C for 400 hours. After that, they were removed from the heating chamber and cooled to room temperature, after which the weight of the test specimens was measured again, and the weight loss rate before and after heating was calculated using the following formula. Formula: {(weight before heating) - (weight after heating)} ÷ (weight before heating) x 100%

[0038] <Oleic acid resistance> The test piece used was a sheet-like test piece with a length and width of 30 mm x width of 120 mm and a thickness of 2 mm, prepared by the method described above. The weight of the test piece was measured in advance, and it was immersed in oleic acid in a container and kept in a thermostatic chamber at 80°C for 70 hours. After that, it was removed from the container, the oleic acid was wiped off, and the weight of the test piece was measured again, and the weight loss rate before and after immersion was calculated using the following formula. Formula: {(weight before immersion) - (weight after immersion)} ÷ (weight before immersion) x 100%

[0039] It is known that human sebum and sweat contain large amounts of oleic acid, and low solubility in oleic acid (low weight loss rate) indicates that the test piece has excellent resistance to oleic acid, meaning that the test piece is less susceptible to discoloration and deterioration after sebum or sweat adheres to it.

[0040] [Table 1]

[0041] In the PVC composition of Example 1, the content of the trimellitic acid-based plasticizer relative to the total of the trimellitic acid-based plasticizer and the polyester-based plasticizer was 67%, and the solubility in oleic acid was sufficiently suppressed compared to Comparative Example 1. In addition, the brittleness temperature was sufficiently low, and the cold resistance was also excellent. Furthermore, the weight loss rate before and after heating was sufficiently low, and the heat resistance was also excellent. In the PVC composition of Example 2, the content of the trimellitic acid-based plasticizer relative to the total of the trimellitic acid-based plasticizer and the polyester-based plasticizer was 50%, and the solubility in oleic acid was suppressed more than in Example 1. In addition, the brittleness temperature was sufficiently low and the cold resistance was excellent. Furthermore, the weight loss rate before and after heating was sufficiently low and the heat resistance was also excellent. In the PVC composition of Example 3, the content of the trimellitic acid-based plasticizer relative to the total of the trimellitic acid-based plasticizer and the polyester-based plasticizer was 33%, and the solubility in oleic acid was further suppressed compared to Examples 1 and 2. In addition, the brittleness temperature was equivalent to that of Comparative Example 2, and the cold resistance was also good. Furthermore, the weight loss rate before and after heating was lower than that of Comparative Example 2, and the heat resistance was also excellent.

[0042] The PVC composition of Comparative Example 1 does not contain a polyester-based plasticizer, and therefore, although the total plasticizer content is the same as in Examples 1 to 3, it has high solubility in oleic acid and it is clear that discoloration and deterioration after sebum or sweat adheres to the test specimen cannot be suppressed. The PVC composition of Comparative Example 2 did not contain a trimellitic acid-based plasticizer, and therefore, although the total plasticizer content was the same as in Examples 1 to 3, it showed a high weight loss rate before and after heating and was clearly inferior in heat resistance.

Claims

1. A vinyl chloride resin composition comprising a vinyl chloride resin, a trimellitic acid plasticizer, and a polyester plasticizer, The vinyl chloride resin composition, wherein the content of the trimellitic acid-based plasticizer is 30 to 70 mass% based on the total content of the trimellitic acid-based plasticizer and the polyester-based plasticizer.

2. 2. The vinyl chloride resin composition according to claim 1, wherein the trimellitic acid-based plasticizer has a linear alkyl group in the molecule.

3. 3. The vinyl chloride resin composition according to claim 2, having a brittle temperature of −35° C. or lower, measured in accordance with JIS K 7216:1980.

4. 4. The vinyl chloride resin composition according to claim 3, wherein the polyester plasticizer has a viscosity of 1000 to 5000 mPa·s at 25°C.

5. 5. The vinyl chloride resin composition according to claim 4, wherein, in a heat resistance test in which a test piece obtained by molding the vinyl chloride resin composition into a sheet is kept in a heating chamber at 120°C for 400 hours, a weight reduction rate, expressed as the weight of the test piece after the heat resistance test relative to the weight of the test piece before the heat resistance test, is 2.0% by weight or less.

6. 6. The vinyl chloride resin composition according to claim 5, wherein in a test in which a test piece obtained by molding the vinyl chloride resin composition into a sheet is immersed in oleic acid at 80° C. for 70 hours, a weight reduction rate, expressed as the weight of the test piece after immersion relative to the weight of the test piece before immersion, is 20% by weight or less.

Citation Information

Patent Citations

  • Vinyl chloride resin composition

    JP1996165393A

  • Vinyl chloride-based resin composition and coated electric wire using the same

    JP1999140263A

  • Soil-proof sheet

    JP2001098464A

  • Vinyl chloride-based resin composition

    JP2010168409A

  • Plasticizer Composition

    JP2020500996A